Voices of the lost : a novel - Barakāt, Hudá, 1952- (Margellos world republic of letters book., 2021)
Winner of the International Prize for Arabic Fiction, this novel weaves together a series of devastating confessions about life in contemporary Arab society This profound and disturbing novel by acclaimed Lebanese author Hoda Barakat tells the story of characters living on the periphery, battling with poverty, and fighting their own demons. Set in an unnamed, war-torn country, the novel consists of six letters-all intercepted by unintended recipients, all of whom are compelled to write their own letters of confession. An undocumented immigrant writes his former lover. A woman in a hotel writes a man from her past. An escaped torturer recounts his crimes to his mother. A former prostitute writes to her brother. A young queer man recounts to his estranged father his partner's battle with AIDS. Finally, the mailman leaves his own note. Incisive, troubling and deeply human, this is an urgent story of lives intimately woven together in a society that is tearing itself apart.